2017
DOI: 10.18632/oncotarget.17863
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide/teriflunomide inhibit Epstein-Barr virus (EBV)-induced lymphoproliferative disease and lytic viral replication

Abstract: EBV infection causes mononucleosis and is associated with specific subsets of B cell lymphomas. Immunosuppressed patients such as organ transplant recipients are particularly susceptible to EBV-induced lymphoproliferative disease (LPD), which can be fatal. Leflunomide (a drug used to treat rheumatoid arthritis) and its active metabolite teriflunomide (used to treat multiple sclerosis) inhibit de novo pyrimidine synthesis by targeting the cellular dihydroorotate dehydrogenase, thereby decreasing T cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 59 publications
(76 reference statements)
1
56
0
Order By: Relevance
“…Some of the KSHVassociated malignancies, like Kaposi sarcoma, seem to depend on lytic replication of this virus 123 . Targeting of early lytic antigen expression might provide a promising novel strategy for the treatment of both EBV and KSHV associated tumors 124 .…”
Section: [H1] Conclusionmentioning
confidence: 99%
“…Some of the KSHVassociated malignancies, like Kaposi sarcoma, seem to depend on lytic replication of this virus 123 . Targeting of early lytic antigen expression might provide a promising novel strategy for the treatment of both EBV and KSHV associated tumors 124 .…”
Section: [H1] Conclusionmentioning
confidence: 99%
“…LEF can significantly reduce CMV-induced apoptosis of the infected cells, interfering with the spreading of the virus [111]. Bilger et al showed that teriflunomide can have a role against Epstein-Barr virus (EBV) [112]. Drug concentrations lower than those normally used for treatment of RA can prevent EBVtransformed human B cell proliferation thanks to an "on target" mechanism on B cells and an "off target" action that alter EBV latency protein expression.…”
Section: Leflunomidementioning
confidence: 99%
“…Drug concentrations lower than those normally used for treatment of RA can prevent EBVtransformed human B cell proliferation thanks to an "on target" mechanism on B cells and an "off target" action that alter EBV latency protein expression. In fact, an increased expression of EBV nuclear antigen-2 (EBNA2) and latent membrane protein-1 (LMP1), the latter able to inhibit B cell proliferation, were observed [112]. Furthermore, teriflunomide induces expression of p53 and cleavage level of PARP, promoting apoptosis of lymphocytes in vitro.…”
Section: Leflunomidementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is emerging evidence suggesting a direct antiviral effect for teri unomide and other DHODH inhibitors against a range of viruses such as Theiler's, virulent Newcastle disease, respiratory syncytial, Ebola, cytomegalovirus, Epstein-Barr, and picornavirus (foot-and-mouth disease) [25][26][27][28]. Moreover, a preliminary pre-clinical study suggests that teri unomide could combat COVID-19 though dual antiviral and immunomodulatory actions [29].…”
Section: Discussionmentioning
confidence: 99%